Agatha Christie's Poirot. Death on the Nile [videorecording (DVD)] - Wilson, Andy, 1958-; Suchet, David; Fox, James, 1939-; Griffiths Malin, Emma, 1981-; Christie, Agatha, 1890-1976 (A & E Home Video ; Distributed by New Video, 2005)
"Death on the Nile": A pleasure cruise down the Nile turns deadly when a murder is discovered on board.